Clinical presentation, investigation findings, and outcomes of hypophysitis in sarcoidosis: a systematic review - Julia F B Cavalcanti; Sara Caixeta de Souza; Leandro Tavares Lucato; Andrea Glezer; Guilherme Diogo Silva (Pituitary, 2026)
Abstract Purpose Hypophysitis in sarcoidosis is a rare manifestation of neurosarcoidosis that may cause permanent endocrine dysfunction, visual impairment, and neurological morbidity. We performed a systematic review to characterize its clinical presentation, diagnostic findings, treatment, and outcomes. Methods PubMed, Embase, and Scopus were searched from inception to January 22, 2025, for reports of adult patients with sarcoidosis-related hypophysitis. Cases were reassessed according to the 2018 Neurosarcoidosis Consortium Consensus Group criteria. Individual patient data were extracted regarding clinical manifestations, hormonal abnormalities, imaging findings, systemic involvement, treatment, recurrence, and long-term outcomes. Sensitivity analyses restricted the cohort to patients meeting definite or probable criteria and stratified cases by publication era (1954–1999, 2000–2017, 2018–2024) to assess the robustness of findings and the impact of temporal heterogeneity. Results A total of 166 studies comprising 274 patients were included. Diagnostic certainty was definite in 26.3%, probable in 47.8%, and possible in 25.9% of cases. Median age was 37 years (IQR 28–48), and 53.5% were male. AVP deficiency was the most frequent manifestation (53.6%), followed by gonadal dysfunction (38.3%), visual loss (36.1%), headache (32.2%), and fatigue (30.5%). Central hypogonadism was the most common anterior pituitary abnormality (74.1%), followed by central hypothyroidism (63.6%) and hyperprolactinemia (58.1%). MRI most commonly demonstrated pituitary stalk thickening (43.1%) and sellar/suprasellar masses (36.4%). CSF analysis frequently showed elevated protein (68.9%) and pleocytosis (59.5%). Systemic involvement occurred in 80.3% of patients, predominantly affecting lymph nodes and lungs. Although corticosteroids were the mainstay of treatment, recurrence occurred in 43.1% of patients, chronic hormone replacement was required in 36.2%, and long-term desmopressin dependence occurred in 30.5%. Findings were materially unchanged when restricted to the definite/probable cohort ( n = 203) and across publication eras, despite increased MRI use and greater adoption of steroid-sparing and biologic therapies over time. Conclusions Hypophysitis in sarcoidosis should be suspected in patients presenting with stalk thickening, sellar lesions, AVP deficiency, or unexplained hypogonadism. Because serum and CSF biomarkers showed limited sensitivity, systemic investigation and extracranial biopsy are essential. Despite treatment, recurrence and persistent endocrine dysfunction remain common, highlighting the need for long-term multidisciplinary follow-up.